Pros and cons of using anonymised linked routine data to improve efficiency of randomised controlled trials in healthcare: experience in primary and emergency care. (19th November 2019) - Snooks, Helen; Watkins, Alan; Jones, Matthew; Khanom, Ashrafunessa; Jones, Jenna; Lyons, Ronan A
No abstract available